2010
DOI: 10.1063/1.3482040
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index dispersion, optical transmittance, and Raman scattering of BaTi2O5 glass

Abstract: The optical and vibrational properties of BaTi2O5 glass prepared by containerless processing were investigated. The refractive index was 2.15 and the Abbe number was 21.5, as measured by the focal method. The glass was transparent from 340 nm to 7.7 μm. From the Raman scattering spectrum, the maximum phonon energy was found to be 829 cm−1. Using these data, fundamental optical parameters such as the optical basicity, the average oscillator strength, and the optical band gap were estimated. These parameters sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
66
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 37 publications
2
66
0
1
Order By: Relevance
“…Glasses with high refractive index and good transmittance from visible to infrared light region have prospective applications in optical devices such as smart phones, endoscopes, mini size laser, optical lithography and so on [1][2][3][4]. Studies proved that heavy metal compositions favor for high refractive index glasses [5][6][7]. However, samples with high content of heavy metal elements are hard to vitrify by conventional melting and solidification methods in the containers without glass network formers such as SiO 2 , B 2 O 3 , or P 2 O 5 [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glasses with high refractive index and good transmittance from visible to infrared light region have prospective applications in optical devices such as smart phones, endoscopes, mini size laser, optical lithography and so on [1][2][3][4]. Studies proved that heavy metal compositions favor for high refractive index glasses [5][6][7]. However, samples with high content of heavy metal elements are hard to vitrify by conventional melting and solidification methods in the containers without glass network formers such as SiO 2 , B 2 O 3 , or P 2 O 5 [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [11] successfully prepared BaTi 2 O 5 glass by using containerless processing, and proved that the average coordination number of Ti-O was approximately 5, and the phase transitions performed a strong influence on permittivity. Masuno [5] found that the refractive index of BaTi 2 O 5 glass was 2.15, the Abbe number was 21.5, and the optical transmittance could be measured from 340 nm to 7.7 μm. Arai [17] demonstrated that the colorless and transparent spherical La 4 Ti 9 O 24 glass could be prepared by using an aerodynamic levitation furnace.…”
Section: Introductionmentioning
confidence: 99%
“…Containerless processing enables glass formation of materials with a low glass forming ability because it prevents heterogeneous nucleation from the container walls and thus promotes deeper undercooling of the melt. Some binary systems, such as Al 2 O 3 -based [7,8], TiO 2 -based [9][10][11][12][13], and Nb 2 O 5 -based glasses [14], have been vitrified in bulk form without the use of network-former oxides by utilizing containerless processing.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 is often used as a component in melt-derived mixed oxide glasses to increase refractive index [14], or as a nucleating agent in glass-ceramics [15,16]. [19]) polyhedra, while in amorphous TiO 2 , Ti is found to have an average coordination number laying between five and six [20] (dependent upon growth method).…”
Section: Introductionmentioning
confidence: 99%